The structure of morpho-functional conditions determining the level of sports performance of young badminton players - Jaworski, J.; Zak, M. (Journal of Human Kinetics, 2015)
The aim of the study was to determine the structure of morpho-functional models that determine the level of sports performance in three consecutive stages of training of young badminton players. In the course of the study, 3 groups of young badminton players were examined: 40 preadolescents aged 11-13, 32 adolescents aged 14-16, and 24 adolescents aged 17-19. The scope of the study involved basic anthropometric measurements, computer tests analysing motor coordination abilities, motor skills encompassing speed, muscular power and strength, and cardiorespiratory endurance. Results of the study indicate that the structure of morpho-functional models varies at different stages of sports training. Sets of variables determining sports performance create characteristic complexes of variables that do not constitute permanent models. The dominance of somatic features and coordination abilities in the early stages of badminton training changes for the benefit of speed and strength abilities.